2020
DOI: 10.1055/a-1263-1742
|View full text |Cite|
|
Sign up to set email alerts
|

Injuries to the Coronoid Process of the Ulna with Involvement of the Lesser Sigmoid Notch

Abstract: Introduction This study aimed to describe the involvement of the lesser sigmoid notch in fractures to the coronoid process. We hypothesized that injuries to the lateral aspect of the coronoid process regularly involve the annular ligament insertion at the anterior lesser sigmoid notch. Material and Methods Patients treated for a coronoid process fracture at our institution between 06/2011 and 07/2018 were included. We excluded patients < 18 years, patients with arthritic changes or previous operat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
(41 reference statements)
0
2
0
Order By: Relevance
“…Studies that focus on fractures involving the RN are rare. In a retrospective analysis of 72 patients with CP fractures, Rausch et al [ 15 ] found a RN involvement in 29% of cases. However, the exact localization of the fracture within the RN and to what amount the RN was fractured was not examined.…”
Section: Discussionmentioning
confidence: 99%
“…Studies that focus on fractures involving the RN are rare. In a retrospective analysis of 72 patients with CP fractures, Rausch et al [ 15 ] found a RN involvement in 29% of cases. However, the exact localization of the fracture within the RN and to what amount the RN was fractured was not examined.…”
Section: Discussionmentioning
confidence: 99%
“…It is considered necessary to repair this type of coronal process fracture in the early stage of injury. 7 However, it is occasionally difficult to determine whether type I or II coronoid process fractures are the vital factors of elbow joint instability. 8 Especially during the early stage of injury, patients cannot undergo muscle strength testing because of severe pain and swelling of the elbow, which increases the difficulty of evaluating the incidence and identifying the causes of elbow joint instability.…”
Section: Indications For Reconstruction Of the Coronoid Process Of The Ulnamentioning
confidence: 99%